Effect of digital technologies on the efficiency of the independent work of linguistics students in the context of distance learning - Sinyukov, Vasily Alekseevich; Kamarova, Nagbdu; Konkol, Marina M.; Suslov, Alexey Viktorovich; Rebro, Olga Vladimirovna (Universidade Estadual Paulista, 2021)
The relevance of the problem of using digital technologies in the independent work of students is because, during the period of study at the university, the fundamentals of professionalism are laid, and the skills of independent professional activity are formed. The purpose of the present article is to determine the effect of the didactic capabilities of digital technologies on the effectiveness and efficiency of the independent work process of linguist students in the context of distance learning. Based on the theoretical analysis of scientific sources devoted to the study of the possibility of using digital technologies in the students’ independent work process, the article presents the main approaches to the definition of the concept of students’ independent work and the main areas of using digital technologies in educational activities. It is concluded that using digital technologies in the organization of students’ independent work allows enhancing their work and leads to an increase in the results of distance learning.